PROBLEMS IN THE ACTIVITY OF NON-BANK CREDIT ORGANIZATIONS IN UZBEKISTAN AND THEIR SOLUTIONS - Dusboev Utkir Khidirovich (Journals Park Publishing, 2024)
This article describes the economic and legal framework of microfinance organizations and their stages of activity development, the specifics of their activities, the ongoing reforms in the development of microfinance organizations in our country. Also, practical recommendations have been developed to address the problems in the development of the market of microfinance services in our country.